2018
DOI: 10.1002/jctb.5687
|View full text |Cite
|
Sign up to set email alerts
|

Re‐using bauxite residues: benefits beyond (critical raw) material recovery

Abstract: Since the world economy has been confronted with an increasing risk of supply shortages of critical raw materials (CRMs), there has been a major interest in identifying alternative secondary sources of CRMs. Bauxite residues from alumina production are available at a multi‐million tonnes scale worldwide. So far, attempts have been made to find alternative re‐use applications for bauxite residues, for instance in cement / pig iron production. However, bauxite residues also constitute an untapped secondary sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 139 publications
(316 reference statements)
0
66
0
Order By: Relevance
“…It is emphasized here that the reduction of Fe 2 O 3 and Fe 3 O 4 by CO (g) through reactions [3] and [5] is more feasible than reactions [2] and [4]. FeO and even Fe can be also formed in solid state; however, we here assume that Fe is mainly produced from FeO in the slag.…”
Section: B Smelting-reduction Thermochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It is emphasized here that the reduction of Fe 2 O 3 and Fe 3 O 4 by CO (g) through reactions [3] and [5] is more feasible than reactions [2] and [4]. FeO and even Fe can be also formed in solid state; however, we here assume that Fe is mainly produced from FeO in the slag.…”
Section: B Smelting-reduction Thermochemistrymentioning
confidence: 99%
“…[1] A large number of efforts have been made to valorize this most-abundant industrial byproduct in the world in building materials, [2] using it as the rare earth element's source, [3] producing green direct-reduced iron (DRI), [4] consuming inorganic polymers and pozzolanic material, [5] and so on. However, none of these fields has moved to a large-scale commercial production due to economic reasons and particular challenges in processing the red mud.…”
Section: Introductionmentioning
confidence: 99%
“…Red mud is an industrial by‐product of the Bayer process, which produces alumina from bauxite ore. A total of 1–1.5 Mg of red mud is generated as a by‐product to obtain 1 Mg of alumina . As the inventory of red mud increases, effective storage and processing solutions are required . The disposal and storage of red mud are difficult because it has high alkalinity (pH 10–13) and contains various types of heavy and radioactive elements .…”
Section: Introductionmentioning
confidence: 99%
“…Al, Co, Cu, Pb, Ni, Mg and Zn) and rare earth elements (e.g. Ti, Mo, W and Re) . The experimental results using industrial by‐products showed that leaching methods using microwaves were more efficient than conventional methods …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation